SURSULAPITSCHI AND THE JOURNEY A CONTRIBUTION TO RESEARCH ON CHILDRENS LITERATURE IN HUNGARY - Fekete, Richárd (Tudásmenedzsment, 2024)
In the following brief reflection, I present some of the characteristics of current and recent Hungarian initiatives in childrens literature, based on the institutional framework and internal literary dynamics. The aim is to give the reader a realistic picture of the current state of research in contemporary Hungarian childrens literature. The paper focuses on the opportunities and challenges facing active and prospective researchers in childrens literature. The text describes the impact of the political and literary regime change on the institutional system and research practices in childrens literature; considers the reasons for counterproductive literary historical approaches, discusses the lack of methods of childrens book criticism and psychology, and proposes some modest methodological suggestion for textual analysis. Despite all the difficulties, for example the legacy of the literary history and the the poorer literary output of the nineties, childrens literature research in Hungary is moving in the right direction. So in this text particular attention is paid to the remarkable initiatives, projects and texts in childrens literature especially of the last 15 years.